A survey of the management of neonatal hypoglycaemia within the Australian and New Zealand Neonatal Network. (26th October 2009) - Harris, Deborah L; Weston, Philip J; Battin, Malcolm R; Harding, Jane E
<x xml:space="preserve">Abstract</x> Background: Neonatal hypoglycaemia is a common problem linked to both brain damage and death. There is controversy regarding both the definition of and best treatment for neonatal hypoglycaemia. Aim: To determine current management of neonatal hypoglycaemia within the Australian and New Zealand Neonatal Network (ANZNN). Methods: Four questionnaires were sent to the Director of each of the 45 nurseries within the ANZNN. The Director was asked to complete one questionnaire and give the remaining three to other doctors involved with the management of babies with hypoglycaemia in the nursery. Results: One hundred and eighty surveys were sent and 127 were returned (71%), including at least one from each nursery. Almost all respondents (120, 94%) reported using a protocol to treat hypoglycaemia. Only 2 (2%) reported screening all babies for neonatal hypoglycaemia, with the remainder screening babies at risk. Only 67, (53%) reported that blood glucose levels were tested on an analyser generally considered to be reliable at low levels. Most respondents (99, 78%) reported the clinical threshold for treatment was <2.6 mmol/L. However, when provided with clinical scenarios, respondents reported a variety of interventions, including no treatment. Conclusion: Doctors within the ANZNN are consistent about definition and screening for neonatal hypoglycaemia. However, frequently, the diagnosis is made using unreliable analysers. There is also wide variation in treatment, suggesting a lack of reliable evidence on which to base practice.